2021
DOI: 10.1002/ccr3.4278
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib‐associated renal cyst development may be associated with prolonged progression‐free survival in patients with ALK‐positive non‐small‐cell lung cancer: Case report and review of the literature

Abstract: Non‐small cell lung cancer patients with anaplastic lymphoma kinase or c‐ros oncogene 1 mutations who are treated with the tyrosine kinase inhibitor crizotinib rarely develop crizotinib‐associated renal cysts (CARCs). Here, we present a case report and review of the literature supporting the hypothesis that CARCs may correlate positively with progression‐free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In this regard, crizotinib is a dual c-MET and ALK inhibitor [ 10 , 15 17 ], but accumulating number of case reports demonstrated that crizotinib is associated with development of cystic lesions in the kidneys, liver, and pancreas [ 20 , 24 , 28 – 35 ]. While the mechanism of CARC formation remains to be defined, as proposed by Wiest et al [ 30 ], complete collection of the following information from the advanced NSCLC patients treated with crizotinib is recommended, that is, patient’s general information including age, gender, race/ethnicity, history of renal cysts; clinical information of primary including stage at diagnosis, genetic information, treatment history, treatment response, PFS; tyrosine kinase inhibitor-associated renal cysts including time to diagnosis, laterality, pathology, symptoms, complications, abnormalities in vitals and labs.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, crizotinib is a dual c-MET and ALK inhibitor [ 10 , 15 17 ], but accumulating number of case reports demonstrated that crizotinib is associated with development of cystic lesions in the kidneys, liver, and pancreas [ 20 , 24 , 28 – 35 ]. While the mechanism of CARC formation remains to be defined, as proposed by Wiest et al [ 30 ], complete collection of the following information from the advanced NSCLC patients treated with crizotinib is recommended, that is, patient’s general information including age, gender, race/ethnicity, history of renal cysts; clinical information of primary including stage at diagnosis, genetic information, treatment history, treatment response, PFS; tyrosine kinase inhibitor-associated renal cysts including time to diagnosis, laterality, pathology, symptoms, complications, abnormalities in vitals and labs.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting finding is that prolonged PFS was observed in ALK -fusion NSCLC patients receiving crizotinib with associated renal cystic formation. 32,33 A patient we recently reported from our institution experienced spontaneous regression of crizotinib related renal cysts, after having a total of 19 months of crizotinib treatment with partial response (PR). 32 Four of 10 cases including Wiest NE 33 ,s data report a prolonged median PFS of around 23 months in crizotinib related renal cysts for ALK -rearranged NSCLC patients.…”
Section: First-generation Alk Inhibitor Crizotinibmentioning
confidence: 99%